ANALISIS SISTEM ANTRIAN DAN OPTIMALISASI LAYANAN TELLER (Studi Kasus pada Bank X di Kota Semarang) - Petrus Lajor Ginting; Edy Rahardja (Faculty of Economics and Business Diponegoro University, 2014)
In terms of providing services to customers in the bank, the phenomenon of Queuing isinevitable and often encountered. Where is clearly visible that the number of customerswaiting to be served. the length of the queue make customers feel uncomfortable, becauseit considers the time they wasted their time waiting in line before being served. Effort thathas been done is to develop technology that can provide satisfaction to customers and feltstill not deliver maximum results. One way to reduce the queues are so long is to how tochange an existing queue system.This research uses as much of the sample which is 1349 Bank X at the teller. Thisresearch uses the pattern of arrival poisson and exponential service pattern.The results of this research show the value of Asymp. Sig > real level. Therefore, it canbe concluded that the Bank X pattern of arrival Poisson and service Eksponential pattern.Then the Bank X has been in accordance with the model queue that is used in general. Itis appropriate in the earlier mentioned that the research queueing models is the patternof arrival of Poisson and service Eksponential pattern.Keywords: queue, poisson, exponential